PENERAPAN GROUP INVESTIGATION UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH KONTEKSTUAL BAGI PESERTA DIDIK KELAS X SMA ISLAM NUSANTARA MALANG PADA MATERI PERTIDAKSAMAAN RASIONAL DAN IRRASIONAL - Abdul Halim Fathani; Yuli Ismi Nahdiyati Ilmi; Firul Santriyo (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2020)
This study aims to describe the application of group investigation in improving contextual problem solving in the material rational and irrational inequality of class X students of senior high school Islam Nusantara Malang. This research was conducted on the basis of preliminary tests that have been given before the action of learning. These results indicate a lack of student interest in mathematics, as well as an understanding of mathematical concepts that need to learn rational and irrational inequalities also show less satisfaction. This research is a class action research, which consists of 2 cycles. The subjects of this study consisted of 10 students, with 7 students from the Social Sciences major, and 3 students majoring in Natural Sciences. The research instrument uses question sheets and observation sheets. Data analysis techniques by calculating the completeness of student learning outcomes. The first cycle shows the completeness of student learning outcomes that is equal to 60% of 10 students. Furthermore, in the second cycle increased completeness of student learning outcomes to 80%. So it can be concluded that the Group Investigation is proven to be able to improve the contextual problem solving in the matter of rational and irrational inequality.